Natural organic matter (NOM) fouling characteristics during water treatment with a submerged ultrafiltration membrane reactor: a case study / A. W. Zularisam, A.F. Ismail and M.R. Salim - Zularisam, A. W.; Ismail, A.F.; Salim, M.R. (2006)
Natural organic mailer (NOM) has been claimed as the major membrane foulant in drinking water treatment processes. However, the primary fraction of NOM which is believed to cause membrane fouling and significant influence of rejection mechanisms are still unclear and not yet well-established. The main objective of this study is to evaluate the effect of fractionated NOM and their fouling potentials on the submerged ultrafiltration membrane reactor performance. The membrane fouling characteristics of NOM based on hydraulic resistances (Rcp Rg R R) rejection of UV 254nm. DOC, and flux decline were assessed using 68 kDa MWCO hydrophobic polysulfone (PS) and 50 kDa MWCO hydrophilic cellulose acetate (CA) membranes. Both PS and CA membranes were spun by a simple forced convective dry/wet spinning technique. The Sungai Pontian Kecil river water was taken as a sample and was subjected to non-ionic macro-porous ion exchange resins (DAX-8 and XAD-4). The sample was fractionated into three specific classes which were hydrophilic, transphilic and hydrophilic compounds. Results showed that the low aromatic hydrophilic fraction content of NOM attributed to the worst flux decline despite lesser solute rejection than hydrophobic component. In addition, the PS membrane was surprisingly found to exhibit higher NOM rejection especially for the component with higher SUVA (UV254nm/DOC) despite smaller nominal MWCO posed by the hydrophilic CA membrane. Charge interaction between hydrophobic component and membrane surface plays more important role than steric exclusion mechanism. NOM rejection mechanisms were found to be a function of both membrane type and water characteristics.